2022
DOI: 10.1021/acsami.2c13792
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Stable, Endurable, and Flexible Sb2TexSe3–x Phase Change Devices for Memory Application and Wearable Electronics

Abstract: Flexible memory and wearable electronics represent an emerging technology, thanks to their reliability, compatibility, and superior performance. Here, an Sb2Te x Se3–x (STSe) phase change material was grown on flexible mica, which not only exhibited superior nature in thermal stability for phase change memory application but also revealed novel function performance in wearable electronics, thanks to its excellent mechanical reliability and endurance. The thermal stability of Sb2Te3 was improved obviously with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Meanwhile, the Sb−O bond was observed, which is attributed to film surface oxidation. 52,53 The bond energies of Sb and Te shift to higher values, which is similar to the case of C-doped Sb 2 Te 3 42 and C-doped GST. 54 C−Sb or C−Te bonds with a large electronegativity difference (C: 2.55; Sb: 2.05; Te: 2.10) 55 easily form C-Sb 2 Te.…”
Section: Results and Analysessupporting
confidence: 72%
“…Meanwhile, the Sb−O bond was observed, which is attributed to film surface oxidation. 52,53 The bond energies of Sb and Te shift to higher values, which is similar to the case of C-doped Sb 2 Te 3 42 and C-doped GST. 54 C−Sb or C−Te bonds with a large electronegativity difference (C: 2.55; Sb: 2.05; Te: 2.10) 55 easily form C-Sb 2 Te.…”
Section: Results and Analysessupporting
confidence: 72%
“…Furthermore, when combined with PPC, NPC acts as a complementary component, expanding the functionality of conventional optoelectronic devices and enabling the construction of multifunctional optoelectronic devices. 18–23 However, it should be noted that the reported origin of NPC phenomena is influenced by various external factors, such as temperature, humidity, defect concentration. 24 All these factors exhibit instability and a lack of controllability, posing challenges in achieving precise and controllable NPC and PPC performance within a single sample.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 9(d) shows a schematic of the flexible device structure. Moreover, Li et al reported improved thermal stability in the Sb 2 Te x Se 3−x (STSe) PCM for applications as well as wearable electronics [ 42 ]. As shown in Figure 9(e,f) , the STSe device has an exceptional endurance of over 100 s and a longer retention of over 100 h, demonstrating its excellent operational reliability.…”
Section: Recent Progress In Pcmmentioning
confidence: 99%
“…(f) Variations in device resistance as a function of time. Reproduced by permission from [ 42 ], copyright [2022, ACS].…”
Section: Recent Progress In Pcmmentioning
confidence: 99%